CCNP security SISAS 300-208 official cert guide - Woland, Aaron T.; Redmon, Kevin (Cisco Press, 2015)
CCNP Security SISAS 300-208 Official Cert Guide CCNP Security SISAS 300-208 Official Cert Guide from Cisco Press enables you to succeed on the exam the first time and is the only self-study resource approved by Cisco. Cisco security experts Aaron Woland and Kevin Redmon share preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. This complete study package includes A test-preparation routine proven to help you pass the exam "Do I Know This Already?" quizzes, which enable you to decide how much time you need to spend on each section The powerful Pearson IT Certification Practice Test software, complete with hundreds of well-reviewed, exam-realistic questions, customization options, and detailed performance reports A final preparation chapter, which guides you through tools and resources to help you craft your review and test-taking strategies Study plan suggestions and templates to help you organize and optimize your study time Well regarded for its level of detail, study plans, assessment features, challenging review questions and exercises, video instruction, and hands-on labs, this official study guide helps you master the concepts and techniques that ensure your exam success. Aaron T. Woland, CCIE No. 20113 , is a Principal Engineer and works with the largest Cisco customers all over the world. His primary job responsibilities include Secure Access and Identity deployments with ISE, solution enhancements, standards development, and futures. Aaron is the author of Cisco ISE for BYOD and Secure Unified Access (Cisco Press) and many published white papers and design guides. He is one of the first six members of the Hall of Fame for Distinguished Speakers at Cisco Live, and is a security columnist for Network World, where he blogs on all things related to Identity. Kevin Redmon is a Systems Test Engineer with the Cisco IoT Vertical Solutions Group, specializing in all things security. Previously with the Cisco Systems Development Unit, Kevin supported several iterations of the Cisco Validated Design Guide for BYOD and is the author of Cisco Bring Your Own Device (BYOD) Networking Live Lessons (Cisco Press). Since joining Cisco in October 2000, he has worked closely with several Cisco design organizations, and as Firewall/VPN Customer Support Engineer with the Cisco Technical Assistance Center (TAC). He holds several Cisco certifications and has an issued...